What's wrong with sin? : sin in individual and social perspective from Schleiermacher to theologies of liberation - Nelson, Derek R. (London, UK ; New York : T. and T. Clark, 2009)
This title examines two primary doctrines of sin, posited in the last half-century, the 'structural sin' type and the 'relational self' type. After an introduction to the current discussion on the doctrine of sin, two 19th century rejections of individualistic conceptions of sin are exposited and critiqued. Chapter 2 details Albrecht Ritschl's critique ('structural sin') of F.D.E. Schleiermacher on sin, and Chapter 3 examines John Nevin's critique ('relational self') of Charles Finney's view of sin as violation of the moral government. These two chapters provide a map for reading 20th century doctrines of social sin, contained in the rest of the book. Chapter 4 tracks the development of Latin American liberation theologies of sin, including extensive analyses of Gutierrez, Segundo, Boff. Chapter 5 is an analysis of feminist and womanist writings on sin, including in-depth treatments of Suchocki, Ruether. Criticisms of these thinkers are categorized according to both the structural sin and relational self types.Finally, Chapter 6 offers an analysis of selected developments in doctrines of sin from Asian Christian theologians, especially Korean Minjung theology as a further exemplification of the structural sin type. The book concludes with recommendations drawn from the preceding analyses for further understanding of the social dimensions of sin: the need for clarifying the agential status of a 'social structure'; the moral culpability of a relational self; and, a call to integrate the structural sin and relational self types into a future doctrine of social sin.
Includes bibliographical references (p. [189]-206) and index.
Keywords: Sin